Synchronous fluorescence determination of ferulic acid with Ce(IV) and sodium tripolyphosphate. (7th June 2013) - Meng, F; Liu, P; Huang, F; Wang, L; Wu, X; Shen, L
ABSTRACT In this study, a synchronous fluorescence detection method for ferulic acid (FA) is proposed based on a redox reaction between FA and Ce(IV) sulfate in dilute sulfuric acid medium at room temperature. It was found that FA could reduce Ce(IV) to Ce(III) in acidic medium, and sodium tripolyphosphate could further enhance the intrinsic fluorescence of the Ce(III) produced. The enhanced extent of synchronous fluorescence intensity was in proportion to the concentration of FA over the range 3.0 × 10‐8 to 1.0 × 10‐5 mol/L. The corresponding limit of determination (S/N = 3) was 1.3 × 10‐8 mol/L. The proposed method was applied to the determination of sodium ferulate for injection sample with satisfactory results. Copyright © 2013 John Wiley & Sons, Ltd.